Uji Salinitas untuk Pengujian Kejadian Intrusi Air Laut (Studi Kasus Gili Trawangan) - Fathoni, Ahmad; Romansyah, Erni; Karyanik, Karyanik; Suhairin, Suhairin; Wahyuni, Ida; Marianah, Marianah; Molo, Hasanuddin (Jurnal Agrotek Ummat, 2025)
Seawater intrusion in Gili Trawangan, North Lombok Regency, can be identified through groundwater salinity testing. This study aims to evaluate changes in groundwater salinity values as an indicator of seawater intrusion in the region. The test was conducted by taking well water samples and analyzing them at the Lombok Island Health Laboratory. The results showed that the groundwater salinity value before the water withdrawal project by PT Berkat Air Laut in 2012 was 5.00‰. During the groundwater withdrawal project period (2013-2022), the salinity value increased to 5.71‰, and post-project, the salinity value reached 6.07‰. These findings indicate that groundwater in Gili Trawangan was classified as brackish water from the start, with increasing salinity values indicating seawater intrusion. However, this increase is still in the low category, at 0.71‰ during the project and 0.36‰ post-project, so it is not classified as significant water pollution.